The active reader in classical antiquity (Argos, 2025)
This article proposes that literature in classical antiquity involved a more active role on the part of the reader than we are accustomed to today. Rather than surrender himself to the text, or enter a fictional world, the reader was expected to engage with the author and, as it were, share in the creation of a work's meaning and effects.